ChemInform Abstract: Towards Non‐toxic Solvents for Membrane Preparation: A Review. Issue 41 (7th October 2014) - Figoli, A.; Marino, T.; Simone, S.; Di Nicolo, E.; Li, X.‐M.; Tornaghi, S.; Drioli, E.
Abstract Review: 213 refs.